2016
DOI: 10.4149/bll_2016_077
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-host disease management

Abstract: Graft-versus-host disease (GVHD) remains a major problem of allogeneic hematopoietic-stem cell transplantation (HSCT) and an obstacle for successful outcome. Clinically signifi cant acute GVHD (grade II or higher) developed in 20 to 65 percent of the patients. Death due to this complication accounts for approximately 50 percent of the deaths that are not due to a relapse of the neoplasm. Up to 70 % of patients who survive beyond day 100 develop chronic GVHD and it is the leading cause of nonrelapse mortality m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…In the meantime, verification of clinical protocols dedicated to the transplantation programme was conducted. A preliminary list of nursing protocols has been developed: Oral care[11]CVC management–no-touch technique[12]Food and diet around HSCTChemotherapy extravasation: prevention, management and treatmentPain management[13, 14]Isolation rules[15]GVHD management[16, 17]…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, verification of clinical protocols dedicated to the transplantation programme was conducted. A preliminary list of nursing protocols has been developed: Oral care[11]CVC management–no-touch technique[12]Food and diet around HSCTChemotherapy extravasation: prevention, management and treatmentPain management[13, 14]Isolation rules[15]GVHD management[16, 17]…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were noted by them, where they found that combining the marker and covariate information can improve sensitivity, specificity, and AUC as well as improve the diagnostic performance 26,27 . More importantly, several factors have been introduced as GVHD risk factors of which the patients age is considered to have an influencing role in GVHD 28 . Further, according to the literature review, a number of studies have been demonstrated that gender disparity influence the GVHD incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib disrupts these pathways, and its use in the management of treatment-resistant GvHD has been found to be effective 9. It is used most frequently when there is a sclerotic dermal involvement of chronic GvHD and has been found to be very effective in such cases 10…”
Section: Discussionmentioning
confidence: 99%